A decade of experience in tumors of femur from local resection to amputation - Shanmugam, Subbiah; Balakrishnan, Sathiyaseelan (International Journal of Research in Orthopaedics, 2023)
Background: Femur is the most common site for long bone tumor especially in young adults. The main function of femur is weight bearing and it plays a vital role in stability of gait. Methods: A total of 42 patients underwent surgery for tumors in femur between 2013 and 2022 in our institution. We analysed the demographic data, type of tumor, nature of treatment given, functional outcome, complication rate and nature, recurrence and readmission patterns in those patients. Results: Of the 42 surgeries, 35 were performed for malignant femoral tumor while the remaining seven for benign femoral tumor. Among the 42 patients, 34 underwent treatment for distal femoral tumor and eight for proximal tumor of which 3 patients underwent total femoral resection with reconstruction. Osteosarcoma was the most common malignant tumor. In total, 30 patients underwent custom made endo prosthesis (CMP) reconstruction after bone resection. Nine patients underwent amputation. Among those 30 patients who underwent CMP reconstruction, three patients were salvaged with amputation for tumor recurrence. Considering the age of one patient we did local resection and cementing for a benign tumor. One patient underwent expandable prosthesis reconstruction and one underwent modular prosthesis. Conclusions: Limb salvage surgery in the form of CMP reconstruction has been the standard of care in our institution with a good functional outcome and low morbidity rate. A combination of surgery with adequate clearance, prompt early physiotherapy and better prosthetic design help our patients to resume their day-to-day activities at the earliest.